Effectiveness of symptom management training on caregiving preparedness and burden of family caregivers in-home palliative care: a quasiexperimental study - Rochmawati, Erna; Saun, Akbar U (Universitas Airlangga, 2022)
Introduction. Family caregiving preparedness remains a problem particularly for those who live in rural areas. Such conditions can cause a high burden for the family caregivers. The purpose of this study was to determine the effectiveness of providing home-based palliative care training for family caregivers (HBPC-FC) on caregiving preparedness and burden. Method. This was a quasi-experimental study using a pre-post test with the control group. There were 50 family caregivers (n=25 in the intervention group, n=25 in the controlled group) involved. The preparedness on caregiving was measured using the Caregiving Inventory (CGI) and burden was measured using Caregiving Burden Scale questionnaires. Results. After four weeks of HBPC-FC program, the caregiving preparedness improved significantly in the intervention group. Statistically significant differences in caregiving burden were also found between-group where caregiving burden in the intergention group decreased significantly (P < 0.05). The HBPC-FC program had positive outcomes for family caregivers. Conclusion. Home-based palliative care training on symptom mangement could be utilised as a form to improve family caregivers' readiness in providing care for patients at home.